121k views
3 votes
Can u explain and answer this question for me thanks

Can u explain and answer this question for me thanks-example-1

1 Answer

2 votes

Answer:

f(x)= x-6

g(x)= x^1/2 (x+3) =√x(x+3) = x √x + 3√x

g(x) × f(x)

=(x√x + 3√x) (x-6)

= x²√x -6x√x + 3x√x - 18√x

= x²√x -3x√x - 18 √x

= x^5/2 - 3x^3/2 - 18^1/2

= √x^5 - 3√x^3 - √18 (B)

Note:

√x = x^1/2

x √x = x^1 × √x= x^1+1/2= x^3/2

x²√x= x^2 × x^1/2 = x^2+1/2 = x^ 5/2

I hope this helps

if u have question let me know in comments ^_^

User Hamoudaq
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.